Education and Training for Local Government Officials: Program Evaluation and Its Impact on Bureaucratic Performance - Faria Ruhana; Rian Fauzi; Hariyanto Hariyanto (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
In the context of regional government, education and training programs for government officials have an important role in improving bureaucratic performance and public services. These programs have experienced significant development in line with changes in community needs and the local government environment. This research then aims to look at education and training programs that can be implemented by local government officials, spread their effectiveness, and analyze their impact on bureaucratic performance at the regional level. This research uses a descriptive qualitative approach and relies on secondary data obtained from various relevant research and previous studies. The results of this research found that education and training programs for local government officials have a positive impact on the performance of bureaucracy and public services at the local level. Through the evolution of these programs, local government officials have access to more comprehensive training materials and innovative teaching methods. This positive impact is felt by the community through better quality public services and improved relations between local governments and their communities. However, challenges such as financial constraints and resistance from some local government officials must be overcome. Education and training programs must remain relevant to national policies, follow the dynamics of external factors, and ensure close cooperation to achieve optimal results.